The Kubernetes bible : learn how to deploy and manage Kubernetes across every cloud platform /: learn how to deploy and manage Kubernetes across every cloud platform. (2022) - Kebbani, Nassim; Tylenda, Piotr; McKendrick, Russ
No abstract available